Analisis Dampak Implementasi Program Keluarga Harapan Terhadap Kesejahteraan Keluarga dalam Perspektif Islam - Hidayat, Ali Akbar; Hak, Muhamad Bai'ul; Fadlli, Muhammad Dzul (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
This study aims to analyze the impact of the implementation of the Family Hope Program (PKH) on family welfare from an Islamic perspective. This research was conducted in PKH beneficiary communities in Babussalam Village, Gerung District, West Lombok Regency. This type of research used is qualitative. Data collection techniques with observation, interviews, and documentation. Data analysis techniques using triangulation for data validity. The results of his research show that PKH has a positive impact on the welfare of beneficiary families in the form of fulfilling basic needs (dharuriyat) which are reflected in the five emergency needs, namely protecting religion (hifz al-din), soul (hifz al-nafs), reason (hifz al-'aql ), offspring (hifz al-nasl) and property (hifz al-mal). While the negative impacts are social jealousy, dependence on PKH, and misuse of aid.